Morpho-kinematics of the Molecular Gas in a Quasar Host Galaxy at Redshift Z=0.654 - Tran, Thai Thi; Pham, Tuan-Anh; Darriulat, Pierre; Do, Hoai Thi; Pham, Nhung Tuyet; Pham, Diep Ngoc; Nguyen, Ngoc Bich; Nguyen, Phuong Thi (Communications in Physics, 2021)
e present a new study of archival ALMA observations of the CO(2-1) line emission ofthe host galaxy of quasar RX J1131. The quasar, at redshift z S ∼0.654, is lensed by a foreground galaxy at z L ∼0.30. Particular attention is paid to the mechanism of gravitational lensing. A simple lens model, shown to well reproduce the optical images obtained by the Hubble Space Telescope, is applied to the ALMA CO(2-1) images, providing a tool to understand the uncertainties attached to the evaluation of the source brightness and kinematics. Uncertainties attached to the process of data reduction are carefully evaluated. Evidence for the robustness of previously published results is obtained. A system of polar coordinates is introduced to better match the specificity ofthe imaging process. It provides particularly clear evidence for rotation of the gas contained in the galaxy. A simple rotating disc model is shown to give an excellent overall description of the morpho-kinematics of the source. It gives evidence for a hot spot of emission located near the quasar, overlapping the caustic and corresponding to an enhancement of emission by a factor ∼2.5. The possible presence of a companion galaxy suggested by some previous authors is not confirmed. The rotation curve is studied with reference to the predictions of the disc model. De-tailed comparison between model and observations gives evidence for a more complex dynamics than implied by the model. Doppler velocity dispersion within the beam size in the image plane is found to contribute 60±10 km s −1 to the line width. It accounts for the observed line width when a2- σ cut is applied to the data. However, when using a less severe cut, a significant amount of turbulence may be accommodated, preventing a reliable evaluation of the contribution of turbulence to the line width.